Novel targets for the treatment of relapsing multiple myeloma. Issue 7 (3rd July 2019) - Giuliani, Nicola; Accardi, Fabrizio; Marchica, Valentina; Dalla Palma, Benedetta; Storti, Paola; Toscani, Denise; Vicario, Emanuela; Malavasi, Fabio
ABSTRACT: Introduction : Multiple myeloma (MM) is characterized by the high tendency to relapse and develop drug resistance. Areas covered : This review focused on the main novel targets identified to design drugs for the treatment of relapsing MM patients. CD38 and SLAMF7 are the main surface molecules leading to the development of monoclonal antibodies (mAbs) recently approved for the treatment of relapsing MM patients. B cell maturation antigen (BCMA) is a suitable target for antibody-drug conjugates, bispecific T cell engager mAbs and Chimeric Antigen Receptor (CAR)-T cells. Moreover, the programmed cell death protein 1 (PD)-1/PD-Ligand (PD-L1) expression profile by MM cells and their microenvironment and the use of immune checkpoints inhibitors in MM patients are reported. Finally, the role of histone deacetylase (HDAC), B cell lymphoma (BCL)-2 family proteins and the nuclear transport protein exportin 1 (XPO1) as novel targets are also underlined. The clinical results of the new inhibitors in relapsing MM patients are discussed. Expert opinion : CD38, SLAMF7, and BCMA are the main targets for different immunotherapeutic approaches. Selective inhibitors of HDAC6, BCL-2, and XPO1 are new promising compounds under clinical investigation in relapsing MM patients.